The Impact of Information and Communication Technology (ICT) on Malaysian Economic Growth - Kuppusamy, Mudiarasan (2004)
The study examined whether ICT investment causes Malaysian economy to grow, or vice-versa in different sample periods. In other words, thi study examined whether economic growth leads to increased investment in ICT or does increased ICT investment leads to higher economic growth in Malaysia.